ANALISIS PERBANDINGAN PENERAPAN METODE SAW DAN TOPSIS DALAM PENENTUAN SISWA PENERIMA KARTU INDONESIA PINTAR DI SMPN 16 BATAM - Devina Desliana Siagian; Rika Harman (LPPM Universitas Putera Batam, 2024)
SMPN 16 Batam is one of the schools in the Riau Islands that implements the Smart Indonesia Program through the Smart Indonesia Card. The selection process still uses the manual method based on the Headmaster's knowledge. To minimize errors and get fair results, a decision support system is needed to determine which students are worthy of receiving the Smart Indonesia Card. In this study uses the Simple Additive Weighting (SAW) method and the Technique for Order Preference by Similarity of Ideal Solution (TOPSIS). These two decision making methods were chosen because they have simple calculations. A comparison of the two methods is to see the differences in decision results from them. The criteria used in this study are parent’s income, parent’s completeness status, Integrated Social Welfare Data (DTKS) data status, report grades, and achievements. The alternative data used was 77 datas from 344 datas from SMPN 16 Batam students who received the assistance. Based on the results, it was found that the student who deserved this assistance was Al Furqan Syarifuddin with a result of 0.93 on SAW and 0.206 on TOPSIS. These two methods produce slightly different decisions in the order of student priority but produce top recommendations for students receiving Smart Indonesia Cards.